2007
DOI: 10.1111/j.1524-4741.2007.00418.x
|View full text |Cite
|
Sign up to set email alerts
|

Predictors of Residual Invasive Disease after Core Needle Biopsy Diagnosis of Ductal Carcinoma In Situ

Abstract: Core needle biopsy (CNB) is used to sample both mammographically and ultrasound detected breast lesions. A diagnosis of ductal carcinoma in situ (DCIS) by CNB does not ensure the absence of invasive cancer upon surgical excision and as a result an upstaged patient may need to undergo additional surgery for axillary nodal evaluation. This study evaluates the accuracy of CNB in excluding invasive disease and the preoperative features that predict upstaging of DCIS to invasive breast cancer. Two hundred fifty-fou… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

6
38
2

Year Published

2008
2008
2018
2018

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 61 publications
(46 citation statements)
references
References 39 publications
6
38
2
Order By: Relevance
“…7,17,21 The advantage of assessing the percentage of positive cores over size estimation or the number of positive cores is that a positive ratio is independent of the core sizes and the total number of cores obtained. It has been previously reported that inadequate (or smaller number)cores was associated with a higher upgrading rate, 13,18 although the latter study 18 also showed that core size was not related to missed invasion in the final excision. Whereas the issue of number of cores has not been well documented in this context, it has also been reported to be unrelated to missed invasion.…”
Section: Discussionmentioning
confidence: 73%
See 3 more Smart Citations
“…7,17,21 The advantage of assessing the percentage of positive cores over size estimation or the number of positive cores is that a positive ratio is independent of the core sizes and the total number of cores obtained. It has been previously reported that inadequate (or smaller number)cores was associated with a higher upgrading rate, 13,18 although the latter study 18 also showed that core size was not related to missed invasion in the final excision. Whereas the issue of number of cores has not been well documented in this context, it has also been reported to be unrelated to missed invasion.…”
Section: Discussionmentioning
confidence: 73%
“…Whether these factors are totally insignificant is still debatable, as all of these had been shown to be significant or insignificant in different series. For instance, some studies showed that age, 16 number of cores, 16,21 grade, [7][8][9]11,16,21 architecture, 7,16,21 necrosis, 9,11,16,21 periductal stromal fibrosis or desmoplasia [14][15][16]21 and calcification 16,18 were insignificant, whereas other studies showed the same factors, including number of cores, 13,18 grade, 10,14,15,20 comedo necrosis, 10,11,19 and periductal inflammatory cells infiltrate, 14 to be significant. It seems that prediction of eventual invasion in needle core biopsy showing only DCIS is still fraught with uncertainty.…”
mentioning
confidence: 91%
See 2 more Smart Citations
“…Underestimation of invasive carcinoma in patients with a core biopsy diagnosis of DCIS ranges from 0% to 59%. [18][19][20][21][22][23][24][25][26][27] This prompted us to examine the predictive value of a core biopsy diagnosis of DCIS, particularly the upgrade rate to invasive carcinoma, and to identify any associated factors that meet criteria for inclusion in surveillance clinical trials.…”
mentioning
confidence: 99%